Control of attachment of Pseudomonas aeruginosa and Burkholderia cepacia to surfaces by shear force - Hui, Y.; Narayanan, K.; Dykes, Gary (Water Environment Federation, 2016)
© 2016, Water Environment Federation. All rights reserved.The effect of physical shearing on the attachment of six Pseudomonas aeruginosa strains and six Burkholderia cepacia strains to glass, stainless steel, polystyrene and Teflont was determined. A significant (p < 0.05) decrease in hydrophobicity was apparent for all P. aeruginosa strains (17-36%) and B. cepacia, MS 5 (20%) after shearing. A significant (p < 0.05) decrease in attachment of some P. aeruginosa (0.2-0.5 log CFU/cm2) and B. cepacia (0.2-0.4 log CFU/cm2) strains to some surface types was apparent after shearing. Significant (p < 0.05) correlation was observed for both numbers of flagellated cells and hydrophobicity against attachment to glass, stainless steel and polystyrene for P. aeruginosa while only hydrophobicity showed significant correlation against the same surfaces for B. cepacia. Scanning electron microscopy and protein analysis showed that shearing removed surface proteins from the cells and may have led to the observed changes in hydrophobicity and attachment to abiotic surfaces.